Recent advances in molecular mechanisms of skin wound healing and its treatments - Mamun, Abdullah Al; Shao, Chuxiao; Geng, Peiwu; Wang, Shuanghu; Xiao, Jian (Frontiers in Immunology, 2024)
The skin, being a multifaceted organ, performs a pivotal function in the complicated woundhealing procedure, which encompasses the triggering of several cellular entities and signaling cascades. Aberrations in the typical healing process of wounds may result in atypical scar development and the establishment of a persistent condition, rendering patients more vulnerable to infections. Chronic burns and wounds have a detrimental effect on the overall quality of life of patients, resulting in higher levels of physical discomfort and socio-economic complexities. The occurrence and frequency of prolonged wounds are on the rise as a result of aging people, hence contributing to escalated expenditures within the healthcare system. The clinical evaluation and treatment of chronic wounds continue to pose challenges despite the advancement of different therapeutic approaches. This is mainly owing to the prolonged treatment duration and intricate processes involved in wound healing. Many conventional methods, such as the administration of growth factors, the use of wound dressings, and the application of skin grafts, are used to ease the process of wound healing across diverse wound types. Nevertheless, these therapeutic approaches may only be practical for some wounds, highlighting the need to advance alternative treatment modalities. Novel wound care technologies, such as nanotherapeutics, stem cell treatment, and 3D bioprinting, aim to improve therapeutic efficacy, prioritize skin regeneration, and minimize adverse effects. This review provides an updated overview of recent advancements in chronic wound healing and therapeutic management using innovative approaches.